On Intuitionistic Fuzzy Primary Ideal of a Ring - P. K. Sharma (Pan-American Journal of Mathematics)
The purpose of this paper is to introduce and investigate primary ideal and P-primary ideal in the intuitionistic fuzzy environment and lay down the foundation for the primary decomposition theorem in the intuitionistic fuzzy setting. Also a suitable characterization of intuitionistic fuzzy P-primary ideal will be discussed.